2018
DOI: 10.2174/1389450118666170328115801
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Nanomaterials in Stem Cell Therapy for Some Neurological Diseases

Abstract: Nano-stem cell-based therapy as a promising strategy has the ability to affect neuronal repair and regeneration in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Similarly, research on stem cell therapy utilizing nanoparticles is also on the rise. Because of the small size and target specificity of the nanoparticles, scientists are aiming to treat some neurological diseases using this strategy [108].…”
Section: Gene Therapymentioning
confidence: 99%
“…Similarly, research on stem cell therapy utilizing nanoparticles is also on the rise. Because of the small size and target specificity of the nanoparticles, scientists are aiming to treat some neurological diseases using this strategy [108].…”
Section: Gene Therapymentioning
confidence: 99%
“…Stem cell therapies have been a famous treatment option for various CNS diseases (Lee et al, 2017;Wei et al, 2017;Sonntag et al, 2018;Sugaya and Vaidya, 2018;Zhang et al, 2018).…”
Section: Stem Cell Derived Exosome Is Neuro Protective Via Astrocytesmentioning
confidence: 99%
“…Stem cells have become the primary choice for transplantation therapy because of their "infinite" proliferation and multi-prospective differentiation potential. Moreover, stem cell transplantation therapy has been shown to promote the recovery of damaged tissues [52,53], including spinal cord, heart, brain, and liver. Previous researches have shown that cell proliferation can be found in subventricular zone in rat model disposed by the middle cerebral artery occlusion (MCAO), suggesting that endogenous recovery process is started after stroke [54][55][56][57].…”
Section: Exosomes Transplantation Therapy Directlymentioning
confidence: 99%